2017
DOI: 10.1097/ccm.0000000000002360
|View full text |Cite
|
Sign up to set email alerts
|

A Contemporary Assessment of Acute Mechanical Ventilation in Beijing: Description, Costs, and Outcomes

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 38 publications
1
23
2
5
Order By: Relevance
“…patients. The treatment of mechanical ventilation in critical patients brings also huge medical burden [4] .So far, no specific anti-SARS-CoV-2 drug has been found successfully [8,9] .Therefore, it is extremely important to recognize the predictive risk factors of disease aggravation, identify severe disease early, give scientific and effective treatment programs, block the progression to severe disease, and avoid intubation and invasive mechanical ventilation in critical disease to reduce the case fatality rate. Based on successfully treatment of 97 COVID-19 patients (including 26 severe, 10 critical) in our hospital, we would like to share and discuss our experience in recognizing and intervention of severe early and timely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…patients. The treatment of mechanical ventilation in critical patients brings also huge medical burden [4] .So far, no specific anti-SARS-CoV-2 drug has been found successfully [8,9] .Therefore, it is extremely important to recognize the predictive risk factors of disease aggravation, identify severe disease early, give scientific and effective treatment programs, block the progression to severe disease, and avoid intubation and invasive mechanical ventilation in critical disease to reduce the case fatality rate. Based on successfully treatment of 97 COVID-19 patients (including 26 severe, 10 critical) in our hospital, we would like to share and discuss our experience in recognizing and intervention of severe early and timely.…”
Section: Discussionmentioning
confidence: 99%
“…Up to March 24, 2020, there are 812,18 confirmed patients and 3,281 deaths in 31 provinces in China [1] . In all world, there are 1051,635 confirmed cases and 56,985 confirmed deaths [2] , COVID-19 has a high case fatality rate in severe patients and a huge medical burden caused by invasive mechanical ventilation [3,4] , National Health Commission of the People's Republic of China has issued the relevant diagnosis and treatment guidelines for COVID - 19, which have been updated to the 7th edition [5] ,WHO also referred to the Chinese COVID -19 guidelines for diagnosis and treatment, and proposed internationally oriented advice on diagnosis and treatment [6] . However, with the continuous recognition of this new disease, we believe that the current diagnosis and treatment guidelines still need to be improved, such as the characteristic clinical symptoms of COVID-19, meaningful laboratory examination indicators, the diagnosis basis of covid-19 pneumonia, the limitation of glucocorticoid usage and dosage in treatment, and the choice of mechanical ventilation timing.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of recent studies of health-related costs among Chinese patients with COPD have focused on specific interventions such as mechanical intervention [36], vaccination [37], or specific risk factor such as pollutants [38,39]. One study conducted in 2011 in four Chinese cities among 678 patients with COPD found that poorer quality of life as determined by the EuroQol-5 dimensions (EQ-5D) health questionnaire was significantly linked to increased medical costs [40].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, NPPV has good cost‐effectiveness when used in general wards, which makes it an attractive option for respiratory support in underdeveloped countries . The use of ward‐based NPPV in selected patients can reduce intubation rates, demand for ICU beds, cost of treatment and nursing workload …”
Section: Strategies and Important Issues For Implementation Of Nppv Imentioning
confidence: 99%
“…37 The use of wardbased NPPV in selected patients can reduce intubation rates, demand for ICU beds, cost of treatment and nursing workload. 10,38 During NPPV, patients need to be monitored closely. Where intubation is inevitable, the switch from NPPV to intubation needs to be made early in order to avoid adverse outcomes caused by delayed intubation.…”
Section: Strategies and Important Issues For Implementation Of Nppv Imentioning
confidence: 99%